Subgeometric Ergodicity under Random-Time State-Dependent Drift Conditions - Mokaedi V. Lekgari (Journal of Probability and Statistics)
Motivated by possible applications of Lyapunov techniques in the stability of stochastic networks, subgeometric ergodicity of Markov chains is investigated. In a nutshell, in this study we take a look at f-ergodic general Markov chains, subgeometrically ergodic at rate r, when the random-time Foster-Lyapunov drift conditions on a set of stopping times are satisfied.